FROM STREET CHILDREN TO CHILDREN OF THE STREETS - CHANGING VIEWS OF OUR CHILDREN IN TANZANIA AND BEYOND - Essary, Jessica; Bakuza, Fortidas; Hoot, James; Aunsu, Munisi (Southeast Asia Early Childhood Journal, 2012)
Increasing numbers of children struggle to survive living in the streets of our world. Research can begin to help ameliorate countless lives of these children. However, research to date addresses the needs of street children in a fragmented manner, with each discipline exploring only one aspect of their plight (Thomas de Benitez, 2011). This article reflects a more systematic review of the related literature that examines Tanzanian policies and economic conditions as they relate children of the streets from a variety of disciplines. Authors conclude with recommendations based on the current education systems’ ability to provide greater opportunities for these children